Optimization Of Antifoaming Agent Usage On Co2 Removal Unit Performance To Increase Product Co2 Purity - Amos Rante Salu (International Journal of Health Engineering and Technology, 2026)
CO2 Removal units in the chemical fertilizer industry often experience foaming in the MDEA absorption-desorption process which reduces CO2 absorption efficiency. This study aims to optimize the concentration of PDMS-based antifoaming to minimize CO2 slip and maximize product CO2 purity through SCAFC identification. The experimental method was carried out on an industrial CO2 Removal unit with a population of four main equipment (Absorber, Stripper, HPFD, LPFD) and samples of varying antifoaming concentrations of 100-200 mL per 100 L of solvent. Measurement instruments include Collapse Time (CT) tester, CO2 analyzer, and laboratory tests, analyzed with a comparative multi-location injection approach. The results show the optimal SCAFC at 150 mL with the fastest CT of 12 seconds (Stripper/Absorber), minimum CO2 slip of 0.001%, and product CO2 purity of 99.45-99.50%. The conclusion of the study recommends 150 mL injection on low-pressure-high-temperature equipment for optimal operation of the fertilizer industry.